2017
DOI: 10.12659/msm.907530
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Prevents Nonalcoholic Fatty Liver Disease (NAFLD) and Hyperlipidemia via PI3K/AKT-Dependent Activation of Nuclear Factor (Erythroid-Derived 2)-Like 2 (Nrf2) in Rats

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is a condition characterized by excessive fat accumulation in the form of triglycerides. The incidence of NAFLD and hyperlipidemia, with their associated risks of end-stage liver and cardiovascular diseases, is increasing rapidly. This study aimed to investigate the effects of scutellarin on the experimental NAFLD in high-fat diet fed and chronic stress rats, and its possible mechanism.Material/MethodsSprague-Dawley rats were fed with high-fat diet and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Western blotting demonstrated that miR-199a-3p promoted the expression of LC3BII, suggesting that miR-199a-3p stimulates the autophagy of HUVECs. The PI3K/AKT signaling pathway is associated with the physiological and pathological processes of the body and has important regulatory functions for cell survival, apoptosis and the synthesis and secretion of inflammatory factors (36). It has been reported that PI3K/AKT and its downstream NF-κB signaling pathway promote proliferation, migration and tube formation in endothelial cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting demonstrated that miR-199a-3p promoted the expression of LC3BII, suggesting that miR-199a-3p stimulates the autophagy of HUVECs. The PI3K/AKT signaling pathway is associated with the physiological and pathological processes of the body and has important regulatory functions for cell survival, apoptosis and the synthesis and secretion of inflammatory factors (36). It has been reported that PI3K/AKT and its downstream NF-κB signaling pathway promote proliferation, migration and tube formation in endothelial cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a modulator of PPARγ, apigenin, was also revealed to attenuate NAFLD by Nrf2-associated regulation of oxidative stress and hepatocyte lipid metabolism (Feng et al, 2017). Moreover, for the prevention of NAFLD, scutellarin, which is a natural drug with active components of breviscapine, was shown to be effective by enhancing the Nrf2-mediated antioxidant system in high-fat diet- and chronic stress-subjected rats (Fan et al, 2017).…”
Section: Protective Impact Of Nrf2 In Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…, possesses pharmacological properties such as anti-inflammation [16], antioxidant effects [17], and the inhibition of adipogenesis [18]. SCU exerts antioxidant effects via Nrf2 nuclear translocation and has been found to enhance the expression levels of heme oxygenase 1 (HO-1) [19]. SCU-loaded Chit-DC-VB12 nanoparticles have been found to downregulate the central retinal artery resistivity index and angiogenesis-related proteins' expressions of retinas in type 2 diabetic rats [20].…”
Section: Introductionmentioning
confidence: 99%